Elements, resources and capacities of agricultural production units: from a thoughtful analytical approach - RÍOS PÉREZ, Juan David; RAMÍREZ MOLINA, Reynier Israel; VILLALOBOS ANTÚNEZ, José Vicente; RUIZ GÓMEZ, Gladis Isabel; RAMOS MARTÍNEZ, Yanelis (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT The article discusses the elements, resources and capacities of agricultural production units. Based on the reflexive analytical approach of classical and current theoretical benchmarks. A Subjective interpretation is proposed as a central point to provide tools that contribute to the identification and configuration of elements of a system, resources with what works and organizational capabilities, leading to competitive advantages and interdependence relationships of companies. The findings show that agricultural production units will need to implement strategies to achieve levels of growth that help overcome gaps and problems of hunger and poverty in the world. RESUMEN El artículo analiza los elementos, recursos y capacidades de las unidades de producción agrícola, partiendo del enfoque analítico reflexivo de referentes teóricos disciplinares clásicos y actuales. Se propone una interpretación subjetiva como punto central para brindar herramientas que contribuyan a la identificación y configuración de elementos de un sistema, recursos con los que funcionan y capacidades organizacionales, derivando en ventajas competitivas y relaciones de interdependencia de las empresas. Los hallazgos evidencian que las unidades de producción agrícola deberán implementar estrategias que permitan alcanzar niveles de crecimiento que coadyuven a superar brechas y problemas de hambre y pobreza en el mundo.